European Society of Clinical Microbiology and Infectious Diseases (ESCMID) Fungal Infection Study Group (EFISG) and European Confederation of Medical Mycology (ECMM) 2013 joint guidelines on diagnosis and management of rare and emerging fungal diseases. (April 2014) - Cornely, O. A.; Cuenca‐Estrella, M.; Meis, J. F.; Ullmann, A. J.
Abstract: This guideline is the second in the line of three for fungal diseases by ESCMID and other societies. The guideline tried to follow the AGREE criteria for the development of clinical guidelines. This guideline serves as a European and potentially world‐wide recommendation for the diagnosis and management of rare and emerging fungi. They include mucormycosis, hyalohyphomycosis ( Fusarium, Paecilomyces, Scedosporium, etc.), phaeohyphomycosis ( Alternaria, Bipolaris, Cladosporium, Rhinocladiella, etc.), and emerging yeasts ( Saccharomyces, Trichosporon, Rhodotorula, etc.).